Hubungan Pengetahuan Dan Sikap Ibu Menyusui Dalam Pemberian Asi Esklusif Di Rsia Dwi Sari Lubuk Linggau - Jannah, Miftahul; Iswari, Indra; sari, Liya Lugita (Jurnal Kesehatan Mitra Sekawan, 2024)
The World Health Organisation (WHO) issued child growth standards that were then implemented in all parts of the world. The content is to emphasise the importance of breastfeeding alone to babies from birth to 6 months of age, this means that babies only receive breast milk from the mother or from caregivers who are asked by the mother to breastfeed, without the addition of other liquids or solid foods, except syrups containing vitamins, supplements, minerals or drugs. The purpose of this study was to determine the relationship between knowledge and attitude of breastfeeding mothers in exclusive breastfeeding at RSIA Dwi Sari Lubuk Linggau. This study uses cross sectional research methods The population in this study were all mothers who breastfeed The sample in this study were 84 respondents with purposive sampling technique. This research instrument used a questionnaire. Data analysis was univariate and bivariate. The results showed that respondents who were less knowledgeable were (66.7) respondents' attitudes were not supportive, namely (60.7%) and respondents who did not give exclusive breastfeeding were (69%) It is hoped that health services should provide information in increasing exclusive breastfeeding.